Does board capital improve climate change disclosures? - Cindy Nathalia; Doddy Setiawan (Cogent Business & Management, 2022)
Climate change is a global issue faced by many countries that cause enormous damage. This is the biggest challenge for a sustainable economy so firms have to mitigate the risk of climate change. Climate change disclosures can be a way for firms to gain legitimacy from stakeholders. The purpose of the study is to examine the effect of board capital on climate change disclosures. This study consists of 191 bank-year observations of banks listed on the Indonesia Stock Exchange from 2016-2020. Data were obtained from annual reports, sustainability reports, and company websites and were analyzed using regression. The results of the study show that board capital has a positive effect on climate change disclosures. This study examines the dimensions of board capital separately too consisting of networking, education, and experience owned by the board on climate change disclosures. The result shows that networking, education, and experience of the board have a positive effect on climate change disclosures. The board plays a significant role in disclosing information about climate change, so companies need to pay attention to the quality of the board. The board's extensive network, higher education, and background experience will increase climate change disclosures.
Keywords: 650; board capital; board education; board experience; board networking; climate change disclosures